Hygienic Evaluation of Electrolyzed or Ozonated Water-Washed Apples Stored under Different Temperatures and Relative Humidity Conditions - Jiao Wang; Yuequi Pei; Hyejin Kim; Sung-Yong Hong; Ae-Son Om (Journal of Food Quality)
The presence of spoilage and pathogenic microorganisms is a concern for the safety of apples. In the present study, we evaluated the hygienic status of electrolyzed water (EW)- or ozonated water (OW)-washed apples, which were stored over 2 weeks under the combination of 2 different temperatures (25 and 30°C) and 2 different relative humidity (RH) conditions (85 and 90%). The average numbers of bacteria or fungi from unwashed and washed apples (EW or OW) did not show statistically significant differences at storage for 0, 1, or 2 weeks and had an increased tendency as the storage temperature, RH, and period increased. Identification of fungal isolates from apples revealed 3 main genera (Fusarium sp., Trichoderma sp., and Alternaria sp.) together with 8 minor genera (Meyerozyma sp., Aspergillus sp., Glomerella sp., Neofusicoccum sp., Penicillium sp., Hypoxylon sp., Talaromyces sp., and Coprinellus sp.). Moreover, sensory tests using EW- or OW-washed apples showed that OW did not significantly affect 5 quality characteristics (appearance, taste, flavor, texture, and overall acceptability). Our data suggest that EW or OW washing did not significantly reduce the levels of microorganisms on apples relative to the unwashed and that EW or OW washing did not deteriorate the quality of washed apples.